Investigation of the estrogenic activity of Pueraria candollei variety mirifica extract on rats - Vui, Dao Thi; Hang, Nguyen Thu; Huy, Nguyen Quoc; Tung, Bui Thanh (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Pueraria candollei variety mirifica (PM) has been widely used as ingredient in many rejuvenating products. In this study, we aimed to assess the estrogenic activity of PM extract grown in Vietnam. Methods: Estrogenic activity of PM extract was estimated on immature female rats by using uterotrophic method to measure the weight of the reproductive organs. Estrogenic activity of PM extract also was investigated in mature female ovariectomized rats by evaluating the vaginal cells growth, reproductive organs weight, serum estradiol concentration. Results: Our results showed that PM extract at doses of 100 mg/kg, 200 mg/kg had increased the reproductive organs weight in immature rats and female ovariectomized rats. In addition, PM extract had increased the serum estradiol concentration and the vaginal cells growth by increasing the percentage of keratinocytes in female ovariectomized rats. Conclusions: Our results showed that PM extract has strong estrogenic activity in rats.